3D printed fittings and fluidic modules for customizable droplet generators. Issue 5 (21st January 2019) - Vijayan, Sindhu; Hashimoto, Michinao
Abstract : We developed a rapid method to prototype axisymmetric droplet generators using 3D printed fittings and commercially available components. This simple method allowed generating simple and complex emulsions of varying sizes and configurations. Abstract : We developed a rapid and simple method to fabricate microfluidic non-planar axisymmetric droplet generators using 3D printed fittings and commercially available components. 3D printing allows facile fabrication of microchannels albeit with limitations in the repeatability at low resolutions. In this work, we used 3D printed fitting to arrange the flow in the axisymmetric configuration, while the commercially available needles formed a flow-focusing nozzle as small as 60 μm in diameter. We assembled 3D printed fitting, needle, and soft tubes as different modules to make a single droplet generator. The design of our device allowed for reconfiguration of the modules after fabrication to achieve customized generation of droplets. We produced droplets of varying diameters by switching the standard needles and the minimum diameter of droplet obtained was 332 ± 10 μm for 34 G (ID = 60 μm). Our method allowed for generating complex emulsions ( i.e. double emulsions and compartmented emulsions) by adding 3D printed sub-units with the fluidic connections. Our approach offered characteristics complementary to existing methods to fabricate flow-focusing generators. The standardized needles serving as a module offered well-defined dimensions of the channels not attainable in desktop 3D printers, while the 3D printed components, in turn, offered a facile route to reconfigure and extend the flow pattern in the device. Fabrication can be completed in a plug-and-play manner. Overall, the technology we developed here will provide a standard approachable route to generate customized microfluidic emulsions for specific applications in chemical and biological sciences.